Halal certification paradox: legal inconsistency on pursuing innovation and halal correlation in Indonesia - Atsari, Zahni Hafizh; Hasyyati, Astrid Amidiaputri; Bintang, Sindu Muhammad Maulana; Saputro, Muhamad Rizky Aulia (Universitas Airlangga, 2025)
As the country with the largest Muslim population, Indonesia faces multiple challenges in implementing an effective Halal Product Assurance (JPH) system. Halal Product Assurance (JPH) is key to maintaining public consumer trust in the products they consume. The Indonesian government has already passed a law on Halal Product Assurance (JPH), which is based on Act Number 33 of 2014 on Halal Product Assurance. Although not yet fully implemented, this law has sparked debate regarding its potential impact on micro, small, and medium enterprises (MSMEs) and the designation of the responsible certifying authority. This research employs a normative legal approach, utilizing secondary data. This research aims to examine and analyze the impact of Halal Product Assurance on the micro, small, and medium enterprises (MSMEs). The main issues are, first, whether the mandatory implementation of JPH constitutes a form of state intervention that imposes disproportionate regulatory burdens on MSMEs. Second, which institution holds the legitimate legal authority to issue halal certificates—the Halal Product Assurance Organizing Body (BPJPH) under the Ministry of Religious Affairs or the Indonesian Ulema Council (MUI). The research contributes to the ongoing discourse on regulatory reform in Indonesia’s Halal industry by assessing the implications of state intervention and institutional authority Keywords: Consumer Trust, Halal Product, MSMEs, Regulatory Reform, State Intervention